Social Criticism of Culture versus Popcultural Studies - Mažeikis, Gintautas (Problemos, 2002)
Genesis of cultural studies, controversies between conceptions of Frankfurt critical school and Birmingham centre of Cultural Studies are discussed in the article. The development of topics of cultural studies and changes of values are interpreted there. The “Dialectic of Enlightenment" of M. Horkheimer and Th. Adorno, the ideas of cultural studies, oppositions between culture of masses and popculture are consequently interpreted there. Evolution of industrial culture is characteriscd by opposition elite, masses and consumer culture is interpreted as development of heterotopies and heterogenous subcultures. Evolution of subcultures from symbolism of resistance to pure games of styles and contradictory, polysemantíc flux of modern subculture are discussed in the article. It is supported by the categories of poststructuralism, postmodem philosophy and postcolonial criticism there.